EXPLORING STUDENTS’ NEEDS FOR STEM BASED DIGITAL LEARNING MODELS TO ENHANCE ENGLISH ACADEMIC READING IN 21ST CENTURY - Hijril Ismail (Indonesian EFL Journal, 2025)
Academic reading is an active process that requires engagement with the text. It is a complex skill that demands effort and plays a crucial role in building knowledge and understanding. However, many students struggle with academic reading due to complex sentence structures, abstract concepts, and the need for critical analysis. This study investigates students’ needs for a STEM-based digital learning model to enhance academic English reading in the 21st century. Using a quantitative survey approach, data were collected through a questionnaire consisting of 33 statements distributed to students in the English Education Program, Faculty of Teacher Training and Education, Universitas Muhammadiyah Mataram. Descriptive statistics, including frequency and percentage, were used to analyze the data. The findings reveal that most students recognize the importance of STEM in improving academic reading comprehension and motivation. Digital applications, particularly interactive tools and gamification, were perceived as effective in supporting learning. However, challenges such as technical difficulties, low motivation, and the need for training in digital tools were identified. The study highlights the necessity of structured academic reading support and digital learning resources that align with the curriculum. These findings provide valuable insights into the integration of STEM-based approaches in English language education, emphasizing the need for effective instructional strategies to maximize their benefits.